Topical Applications of Caulerpa spp. Extract Preventing Skin Aging through Improving Skin Moisture, Pigmentation and Decrease Laxity - Anak Agung Gde Putra Wiraguna (Journal of Global Pharma Technology, 2016)
Background: Caulerpa spp. extract contains neoxanthin, free astaxanthin, antheraxanthin, canthaxanthin, astaxanthin monoester, fucoxanthin, astaxanthin diester, and beta carotene, vitamins A, C, and E, minerals, amino acids and polyphenols which are photocemoprotective as to protect skin from damage caused by exposure to UV-B rays. This study aims to determine the effectiveness of topical 0.2% Caulerpa spp. extract in preventing premature skin aging in research subjects assessed by the parameters of skin moisture, pigmentation, and laxity of the skin. Method: This study was purely experimental research, using the randomized double-blind pretest-posttest control group design. A total of 40 research subjects participated in this study and were divided into two groups, namely the treatment group of 20 subjects, who were given interventions in the form of topical 0.2% Caulerpa spp. extract gel on the face, and the control group of 20 subjects who were given intervention in the form of application topical base cream on the face. All groups performed a pretest with a simple A-one scanner to assess skin aging with moisture, pigmentation, and laxity parameters on the skin. The two study groups were then treated for one month and post-tested. The research data was then collected for statistical analysis of using independent t-test and paired sample t-test. Results: Differences in skin assessments were analysed before and after therapy. Differences in assessment before therapy obtained p<0.05 on laxity and pore variables. Differences in assessment after treatment were found to be p<0.05 also in laxity and pores. Test differences in skin assessment in the two groups with Mann-Whitney using the difference in values after and before therapy obtained p<0.05 in pigmentation, laxity, humidity, pores, sebum U zone, and sebum T zone. Conclusion: Topical administration of topical Caulerpa spp. gel on the face has a photo protective effect by reducing pigmentation and laxity and increasing skin moisture.Keywords: Caulerpa spp., Skin aging, Pigmentation, Laxity.